Influence of Mobile Marketing on Customer Purchase Intentions in Emerging Market - Arifin, Andi Harmoko; Khotimah, Khusnul; Supriyadi, Asep; Fauzi, Rizal Ula Ananta; Sinaga, Hommy Dorthy Ellyany (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This study aims to analyze the influence of mobile marketing on consumer purchase intent in emerging markets through a meta-analysis approach. As mobile technology penetrates and the use of the internet on mobile devices, mobile-based marketing strategies are becoming increasingly important, especially in developing countries. The study synthesizes 10 empirical research results published between 2022 and 2025 that meet inclusion criteria, such as topic relevance, completeness of statistical data, and focus on emerging market contexts. The analysis was conducted using a random effects model, which showed that mobile marketing had a significant positive influence on consumer purchase intent (Hedges' g = 1.029; p 0.001), with a moderate effect size. The moderator's analysis showed that factors such as ad personalization, interactivity, and digital literacy levels were variables that strengthened the relationship. The results of this study provide evidence that contextually designed mobile marketing strategies can increase marketing effectiveness in emerging markets, as well as be an important contribution to the digital marketing literature in the digital economy era.